"Comparative study of serum and synovial fluid Oncostatin M level in rheumatoid arthritis and osteoarthritis patients". Issue 3 (September 2022) - Bassyouni, Iman H.; Elessawi, Dina F.; Tawfik, Mohamed S.; Nosseir, Neveen M.
Abstract: Background: Rheumatoid arthritis (RA) remains a long-standing inflammatory syndrome where the joint synovial membrane is inflamed, with subsequent joint deformation. Osteoarthritis (OA) is considered to be a progressive destruction of articular cartilage characterized by severe pain while moving. Oncostatin M (OSM) is a polymorphic cytokine that is part of the interleukin- 6 (IL-6) cytokine group. Oncostatin M stimulates synovitis by enhancing synovial hypertrophy, neovascularization, and infiltration of inflammatory cells. Aim of the work: to evaluate the relationship between serum and synovial OSM levels in rheumatoid arthritis versus osteoarthritis patients and assess this factor as a potential predictor of disease severity and prognosis. Materials and Methods: Thirty-three patients diagnosed with RA were enrolled, satisfying the ACR/EULAR 2010 categorization standards for RA. Thirty-three patients diagnosed with OA according to 1986 ACR standards for knee osteoarthritis were included. Thirty-three healthy subjects were enrolled as controls who were not suffering from joint diseases or any other chronic diseases. Serum and synovial fluid OSM samples were taken from patients with RA and OA attending the Cairo University Hospital rheumatology clinics. Oncostatin M levels were assessed using suitable Enzyme-Linked Immunosorbent Assay (ELISA) kits. Results: Serum levels of OSM in the RA and OA groups of cases were significantly elevated in comparison to the controls (P< 0.001). Serum levels of OSM were significantly elevated compared to synovial OSM in the RA and OA groups of patients (P< 0.001). The serum levels of OSM in the RA group of patients correlated positively with synovial OSM in a significant manner (p<0.00001). The serum levels of OSM in the OA group of patients correlated positively with synovial OSM, but the correlation was not significant (p=0.39). Conclusion: Oncostatin M plays an important part in the development and progression of both RA and OA, so it could be used as a possible biomarker in the evaluation of these diseases' progression.